Between democratic network governance and neoliberalism: A regime-theoretical analysis of collaboration in Barcelona. (April 2015) - Blanco, Ismael
Abstract: Contemporary explanations of urban governance in Europe have underlined the increasing influence of the 'networks paradigm'. For some, urban network governance revitalises local democracy by fostering a more plural, inclusive and participative approach to urban policymaking. For others, the shift towards collaborative governance facilitates the concentration of urban political power and the cooptation of civil society into the rationalities of neoliberalism. This paper argues that such accounts are excessively reductive, failing adequately to recognise the spatio-temporal complexities of urban governance trajectories in Europe. The paper argues that a reinvigorated regime-theoretical approach can help overcome the networks/neoliberalism dualism by showing how different coalitions mobilise different sets of resources over time and in different policy arenas. Prospects for urban democracy are not only determined by the evolution of structural forces like the 2008 crisis or global neoliberalism. They are also influenced by the outcomes of political competition between alternative coalitions within each city. The analysis of the case of Barcelona illustrates the value of such analytical perspective and of the research agenda that stems from it.